Strategi Pembiayaan UMKM Dalam Meningkatkan Usaha Nasabah Pada Masa Covid 19 (Studi Kasus Di PT. Bank Sumut Cabang Syariah Medan Katamaso) - Azhari Akmal Tarigan; Andre Bagaskara (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research is motivated by the development of micro, small and medium enterprises is a way that is considered to have a large role in the development of the national economy. The development of a business will help overcome the unemployment problem, given the large number of MSMEs in this country, so that it can increase job opportunities and opportunities to open businesses, which in turn encourages regional and rural development. In developing MSMEs, PT. Bank Sumut Syariah Medan Katamaso Branch as a financing institution that prioritizes services in supporting the improvement of the community's economy. One of the roles of sharia microfinance in the economic development of the community is by providing financing capital to customers to develop their businesses. This journal discusses the MSME Financing Strategy in Improving Customer Business During the Covid 19 Period (Case Study of PT. Bank Sumut Syariah Branch Medan Katamaso). In this study, the theory of the MSME financing strategy carried out by PT. Bank of North Sumatra Sharia Branch Medan Katamaso. in improving customer business during the Covid 19 period. This type of research is qualitative research, in descriptive form. The data sources used are primary and secondary data sources. Data was collected using interview, documentation, and observation techniques. The results of this study conclude that the MSME financing strategy in increasing customer business during the covid 19 period uses a murabahah contract in the MSME financing strategy, namely banks must manage mitigation appropriately and banks must focus on industries that have prospects to be financed. During the Covid 19 period, business development experienced a rapid decline so that it affected the decline in income for several customer businesses that had done MSME financing at PT. Bank Sumut Sharia Branch Medan Katamaso. In contrast to before the Covid 19 period, which is currently happening, customer business developments are still developing.